Neutrophil as a Carrier for Cancer Nanotherapeutics: A Comparative Study of Liposome, PLGA, and Magnetic Nanoparticles Delivery to Tumors - Garanina, Anastasiia S.; Vishnevskiy, Daniil A.; Chernysheva, Anastasia A.; Valikhov, Marat P.; Malinovskaya, Julia A.; Lazareva, Polina A.; Semkina, Alevtina S.; Abakumov, Maxim A.; Naumenko, Victor A. (Pharmaceuticals (Basel, Switzerland), 2023)
Insufficient drug accumulation in tumors is still a major concern for using cancer nanotherapeutics. Here, the neutrophil-based delivery of three nanoparticle types—liposomes, PLGA, and magnetite nanoparticles—was assessed both in vitro and in vivo. Confocal microscopy and a flow cytometry analysis demonstrated that all the studied nanoparticles interacted with neutrophils from the peripheral blood of mice with 4T1 mammary adenocarcinoma without a significant impact on neutrophil viability or activation state. Intravital microscopy of the tumor microenvironment showed that the neutrophils did not engulf the liposomes after intravenous administration, but facilitated nanoparticle extravasation in tumors through micro- and macroleakages. PLGA accumulated along the vessel walls in the form of local clusters. Later, PLGA nanoparticle-loaded neutrophils were found to cross the vascular barrier and migrate towards the tumor core. The magnetite nanoparticles extravasated in tumors both via spontaneous macroleakages and on neutrophils. Overall, the specific type of nanoparticles largely determined their behavior in blood vessels and their neutrophil-mediated delivery to the tumor. Since neutrophils are the first to migrate to the site of inflammation, they can increase nanodrug delivery effectiveness for nanomedicine application.